(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Diabetes mellitus and hypertension are chronic disorders, inadequate management of these two disorders leads to several complications and end organ damage that can impair health related quality of life (HRQoL) in these individuals. Several studies in hypertensive patients concluded that hypertension reduced HRQoL and participants with diabetes also reported comparably decreased HRQoL. The data on HRQoL in patients suffering from both hypertension and diabetes is limited hence we designed this study to assess health related quality of life in patients suffering from hypertension and diabetes mellitus. Methodology: This single centre, cross-sectional study was conducted for 2 months between April and August 2013 in patients with hypertension and diabetes mellitus. Patients suffering from hypertension were recruited in study and were divided into two groups, Group 1 consisted of patient suffering from hypertension and diabetes mellitus whereas Group 2 consisted of patients suffering from hypertension. Patients were assessed on Short form health Survey (SF-36) and the WHOQOL Bref scores. Results: A total of 85 patients were screened out of which 41 patients were enrolled in the study, 21 patients in Group 1 and 20 patients in group 2. The SF-36 Scores showed significantly (p<0.05) worse pain scores in patients in Group 2. Patients in Group 1 had a better quality of life as compared to other group as evident by higher scores in most of the parameters of SF-36 and WHO-QOL Bref Score, though it was not statistically significant. Conclusion: Both groups had compromised quality of life; patients with hypertension and diabetes had a better quality of life. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.84-89